Supplementation of sugarcane bagasse with rice bran and sugarcane molasses for shiitake (Lentinula edodes) spawn production - Rossi,Ivan Henrique (2003)
The purpose of this study was to assess the myceliation rate, mycelial vigor and "estimated biomass" of Lentinula edodes (Berk.) Pegler, grown on a sugarcane bagasse substrate enriched with rice bran and sugarcane molasses for spawn production. The proportions of rice bran used were 0, 10, 15, 20, 25, 30 and 40% (dry weight/dry weight of bagasse) and the sugarcane molasses concentrations tested were 0, 10, 20, 30, 40, 50 and 60 g/kg (dry weight/dry weight of bagasse plus rice bran). The myceliation rate was decreased by the addition of the higher quantities of rice bran. The 25 and 30% rice bran proportions induced the highest stimulation of mycelial vigor. The addition of sugarcane molasses did not change myceliation rate or mycelial vigor. The "estimated biomass" values were similar when intermediate rice bran proportions were used and for all sugarcane molasses concentrations. Based on response surface obtained for the "estimated biomass" data, higher values were obtained with substrates containing 20 to 25% rice bran combined with 10 to 30 g sugarcane molasses, although the latter supplement was not considered to stimulate L. edodes growth.